Sustainable constructions, environmental impacts (2019)
Sustainable Development Goal 11 seeks to ensure that cities and other human settlements are safe, inclusive, resilient and sustainable, sustainability should be an intrinsic feature of urbanism. In this work, they are presented: The toxins generated by the building materials: the envelope in the buildings (Energy efficiency), durable materials in the building, the clean technologies and the certifications; to conclude: that today, more than ever, to take advantage of technology, the correct use of resources, and sustainable and integral development with environmental responsibility, contains the review of the professional exercise in the field of architecture, engineering, of urban planning and construction, from, the design process, with the selection of materials, under the premise of environmental sustainability and not only for aesthetic and economic reasons. Also besides, teams working in these fields will be forced, in a short time, to use certification systems and tolos such as the ACL as well as the use of utilities, BIM with CAD and scale in the integral management of projects.